Media Pembelajaran Jarak Jauh Dalam Jaringan pada Mata Kuliah Membaca Bahasa Mandarin - Handayani, Siti (Program Studi Pendidikan Bahasa Mandarin, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta, 2022)
The use of applications for online distance learning is a solution that can be used by teachers and students for the implementation of learning during the Covid-19 pandemic. Courses in the Department of Chinese Language Education (PSPBM) are carried out synchronously and asynchronously by utilizing various of online applications that can assist online distance learning. This study aims to describe the usage and utilization of online applications for the Chinese Reading Skills Course in PSPBM, as well as the opinion of teachers and students regarding the use of the online applications. The research method used is descriptive qualitative. Research data are collected through interviews and questionnaires. The respondents of this study are teachers and participants of Basic Chinese Reading Skills Course I-IV in semester 113-114 Academic Year of 2020/2021. The result of the study shows that online distance learning for Basic Chinese Reading Skills Course I-IV in PSPBM during the Covid-19 pandemic can be carried out well. The online applications which can help teachers and students during the learning process are Zoom, Google Classroom, WhatsApp, Wordwall, Quizizz, and Google Form. Although sometimes there are technical obstacles such as an internet network that is less stable and some applications require a lot of internet quota, there are no specific things that hinder the online distance learning process during the Covid-19 pandemic.